2007
DOI: 10.1007/s00232-007-9032-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Cytoplasmic Loop Domain of Cx43 in Its Intracellular Localization and Function: Possible Interaction with Cadherin

Abstract: We have previously shown that intracellular trafficking and function of connexin (Cx) 26 and Cx43 are controlled by E-cadherin. In the present study, we attempted to determine which part of Cx43 is involved in this control mechanism. Since Cx26 has a very short C terminus in the cytoplasm, we hypothesized that the C-terminal domain may not be important for this process and, indeed, found that green fluorescence protein (GFP)-tagged Cx43DeltaC (deleted from the codon 239) moved to the plasma membrane both in P3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…The findings suggested that the expression of cell junction-related proteins such as connexin and par-3 were down-regulated in the tumor tissues and there existed a positive relationship between such expression and the distal margin of resection. Yano and Nambara et al reported the similar findings by tumor cells culture in vitro [10,11] . These findings evidenced that connexin was closely associated with tumorigenesis and tumor differentiation.…”
Section: Discussionsupporting
confidence: 76%
“…The findings suggested that the expression of cell junction-related proteins such as connexin and par-3 were down-regulated in the tumor tissues and there existed a positive relationship between such expression and the distal margin of resection. Yano and Nambara et al reported the similar findings by tumor cells culture in vitro [10,11] . These findings evidenced that connexin was closely associated with tumorigenesis and tumor differentiation.…”
Section: Discussionsupporting
confidence: 76%
“…31 In nonproliferative DR, cadherin-5 expression in the retina is reduced, 32 which may compromise interactions between cadherin and the cytoplasmic loop domain of Cx43. 33 Such altered interactions could compromise barrier characteristics in the retinal vessels. Additionally, because blood-retinal barrier (BRB) breakdown in diabetes involves the decreased expression of tight junction protein ZO-1, 34 which can alter Cx43 function 35 through interaction with the COOH-terminal of Cx43, 36 it is possible that in diabetes, BRB breakdown involves both tight junctions and gap junctions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to tubulin binding (Dai et al, 2007;Giepmans et al, 2001a;Giepmans et al, 2001b;Guo et al, 2003;Johnson et al, 2002;Shaw et al, 2007;Thomas et al, 2001), Cx43 has also been shown to bind ZO-1 (Barker et al, 2002;Giepmans and Moolenaar, 1998), which might explain the redistribution of ZO-1 to the cytoplasm in Cx43 KO epicardial cells. In some cell types, Cx43 is observed to traffic and colocalize with cadherins (Li et al, 2008;Nambara et al, 2007;Wei et al, 2005;Xu et al, 2001).…”
Section: Research Articlementioning
confidence: 99%